Self-directed learning readiness among nurses in Malaysia - Chang, Woan Ching; Eh Jun, Eewern; Souriappan, Evelyn Sharmini; Kanagasundram, Nagani; Mani, Sangeetha (Universitas Fort De Kock Bukittinggi, 2022)
Self-directed learning is one of the important skills for nurses. The readiness to be self-directed in learning enhances nursing professional development and life-long learning. This study aims to determine the level of self-directed learning readiness among nurses at a selected hospital in Malaysia. The conceptual framework for the study is based on the concepts of self-directed learning readiness. This is a cross-sectional quantitative study using descriptive and correlational method for data analysis. A simple random sampling technique was employed to recruit 145 nurses. The Self-Directed Learning Readiness Scale (SDLRS) was adopted to measure the variables of the study. The findings of the study revealed a high level of self-directed learning readiness among nurses (M = 161.71, SD = 12.60). The highest subscale of SDLR was self-control (M=58.22, SD= 4.78) followed by self-management (M=53.99, SD= 4.92) and desire for learning (M=49.51, SD= 4.63). There is a statistically significant difference between age, academic qualification, and self-directed learning readiness (p< 0.05). This study highlights the important concepts of self-directed learning for nurses. The role of educators and administrators is essential to support nurses for self-direction in higher education. Future studies to explore barriers from self-directed learning are recommended.